Manual of practical medicine - Alagappan, R. (Jaypee Brothers Medical Publishers (P) Ltd., 2014)
Fully revised, fifth edition providing recent advances in prevention, diagnosis and treatment of diseases. Organised anatomically with nearly 1000 images, illustrations and tables